Uncertainty and Sensitivity in the Development Lifecycle of Advanced Aerospace Systems - Timothy L. Eddy; Christopher M. VanYe; Beatrice E. Li; Thomas L. Polmateer; Christopher P. Goyne; John Friend; David Barnes; Megan E. Gunn; Igor Linkov; David L. Slutzky; James H. Lambert (IEEE Open Journal of Systems Engineering)
Reliability and assurance of the research enterprise for the development and acquisition of advanced technologies is urgently needed. In particular, aerospace systems are susceptible to endogenous and exogenous disruptions throughout their lifecycles. A principled approach is needed to address sensitivity, trust, security, and risk in the research and development enterprise. A particular concern is for integrated hardware and software devices that are essential to aerospace systems. This article introduces a method for enterprise-level sensitivity analysis of emergent and future conditions that relies on scenario-based preferences to identify the conditions that are most disruptive to the systems acquisition schedule. We demonstrate the method via a comprehensive analysis for the acquisition of advanced hypersonic glide vehicle technologies using thirteen importance/ordering criteria, forty initiatives, and ten scenarios. The approach and results are applicable to reliability assurance and management for a variety of high technology systems. Additionally, the approach is applicable to enterprise reliability and assurance improvements for supply chains, manufacturing, maintenance, repair, etc.